Mild hyperprolactinemia in women with polycystic ovary syndrome. Insights from a large cross-sectional study - Luque-Ramírez, Manuel; Quintero-Tobar, Alejandra; Martínez-García, María Ángeles; de Lope Quiñones, Sara; Insenser, María; Nattero-Chávez, Lía; Escobar-Morreale, Héctor Francisco (Journal of clinical & translational endocrinology, 2025)
•Hyperprolactinemia is an uncommon feature in polycystic ovary syndrome, despite this condition is argued to induce mild prolactin elevations.•Venipuncture stress and macroprolactin are the primary causes of hyperprolactinemia in polycystic ovary syndrome.•Polycystic ovary syndrome can still be diagnosed even with mild elevation in circulating prolactin when suggestive symptoms are present. Hyperprolactinemia is an exclusion criterion for polycystic ovary syndrome (PCOS), albeit PCOS itself is argued to induce mild hyperprolactinemia. We aimed to study the prevalence and causes of hyperprolactinemia in patients with PCOS. We conducted a cross-sectional study including 336 premenopausal patients with PCOS and 90 nonhyperandrogenic controls referred to our clinics (referral population). We also studied an unselected population of premenopausal individuals who attended our center for voluntary blood donation (14 patients with PCOS and 207 non-hyperandrogenic controls). The main outcome measure was the percentage of individuals with hyperprolactinemia. As a whole, 39 out of 647 participants showed increased basal prolactin concentrations (6.0%, 95%CI: 4.4; 8.1) regardless of having PCOS or being a control, in both referral and unselected populations. In the referral population, 18 out of 31 individuals with hyperprolactinemia (58.0%, 95%CI: 40.8; 73.6) showed normal prolactin concentrations after appropriate resting, suggesting venipuncture stress-related hyperprolactinemia, and another nine participants (29.0%, 95%IC: 16.1; 46.6) did so after pre-analytical polyethylene-glycol precipitation of serum, indicating macroprolactinemia. There were differences in these figures between patients with PCOS and controls. In the unselected population, three out of eight participants with hyperprolactinemia (37.5%, 95%IC: 13.7; 69.4) had macroprolactinemia, and stress-related hyperprolactinemia accounted for another 62.5% (95%IC: 30.6; 86.3) of cases. Hyperprolactinemia is equally likely among patients with PCOS and non-hyperandrogenic individuals. The most common causes of mild hyperprolactinemia in this population are venipuncture stress and macroprolactinemia that must not preclude a diagnosis of PCOS if suggested by signs and symptoms.